REGIONAL ECONOMIC ASSESSMENT OF THE PLANNED DE BEERS PASS ROAD PROJECT IN SOUTH AFRICA - Pienaar, Wessel (The South African Journal of Industrial Engineering, 2016)
This article analyses the magnitude of the possible regional economic impacts that might stem from the proposed De Beers Pass Route (DBPR) project in South Africa. The regional income multiplier and income accelerator analysis are used to estimate the gross and net once-off increase in regional income during construction, and the recurring increases in regional income during road use. The difference between a cost–benefit analysis and a regional economic income analysis is indicated. To end, guiding pointers are supplied on the appropriate use of independent variables when applying the regional income multiplier-accelerator model.